Ultrastructural platelet disorders in patients with type 2 diabetes mellitus and hypertension. - Pertseva, N. O. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Disorders of hemostasis in patients with arterial hypertension and diabetes mellitus type 2 are complex: growing aggregative activity of platelets and red blood cells, activation and degranulation of platelet antiaggregatory potential endothelium; reduced anticoagulant and fibrinolytic activity of blood. Objective. The purpose of this study was to determine the morphological changes of blood cells in patients with type 2 diabetes mellitus with hypertension. Methods. Ultrastructural analysis of platelets was performed in 60 patients with type 2 diabetes mellitus and hypertension and 5 volunteers – healthy individuals (control group). Results. The degree of alteration of platelet hemostasis depends on the quality level of glycemic control and albuminuria. Patients with optimal glycemic control, there is significantly increased relative content of activated platelets with preservation of normal and degranulated content aggregated forms and the appearance of individual platelets with alpha and delta granules imbalance. In patients with albuminuria and poor glycemic control has been a sharp violation of platelet hemostasis due to significant increase of the content of activated, degranulated and aggregated platelets release the contents of the majority of the granules, the development of intravascular hyperactivation of platelets, increasing the number of reversibly and irreversibly transformed erythrocytes, including the appearance of platelet-leukocyte aggregates. Conclusion. Morphological substrate of platelet hemostasis damage in patients with type 2 diabetes mellitus with hypertension is complex of ultrastructural changes of blood cells: intravascular platelet hyperactivation, an imbalance content of all types of granules, transformation of the red blood surface architecture, and the formation of different composition and size of platelet aggregates. This complex is found in all patients of this contingent and acts as an early predictor of the disease. The most sensitive quantitative characteristics of this complex is the relative content of activated and aggregated platelets, packing density of alpha- and delta-granules, level of inversely transformed red blood cells, the number of platelet aggregates.